Assessing the economic impact of traction voltage choice for Slovenian public railway infrastructure - Aver, Boštjan (Advances in business related scientific research journal, 2026)
Driven by the green transition, we are currently witnessing intensified investment in railway infrastructure and efforts to enhance interoperability with the European network. This paper evaluates the economic feasibility of transitioning to alternative traction power supply systems (15 kV or 25 kV). Such a transition aims to bolster energy efficiency, strengthen competitiveness, and improve Slovenia’s integration into key European transport corridors.
Keywords: economic analysis; energy efficiency; public railway infrastructure; Slovenian railway network; traction power supply system